STRATEGI PENGELOLAAN HUTAN RAKYAT DI KABUPATEN MAROS - Muhammad Yusuf; St Subaedah; Saida Saida (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
This study aims to determine external and internal factors in community forest management in Maros Regency, formulate community forest development strategies through involvement with stakeholders in Maros Regency and to analyze steps that need to be used as a reference and policy recommendation for community forest management in the Regency. Maros. Data retrieval in this study was carried out by a survey method which was conducted with a questionnaire for business actors or farmer groups, while interviews were for agricultural and forestry extension agents, including the village government. The sample was determined by purposive sampling by determining 50 respondents of community forest management farmers. Each of 25 people per district, each sub-district is represented by 5 groups and 1 group consisting of 5 people, namely the Chairperson, Secretary, Treasurer plus 2 members. The analysis used in this research is descriptive statistical analysis, SWOT analysis (strength, weakness, opportunity, threat). The results of the analysis show that there are two strategic priorities that can be applied, namely (1) strengthening the role of the group by providing accurate market information; (2) provide forestry counseling and guidance from the government for area arrangement and management plan preparation; (3) The government facilitates licensing to establish a timber industry in order to increase the value price of wood; and (4) Using agroforestry patterns.